DESCRIPTION OF THE CONCEPTUAL CHANGES IN CHEMICAL PRE-SERVICE TEACHERS IN UNIVERSITY OF TANJUNG PURA USING LEARNING 5E CYCLE MODEL ON REACTION RATE MATERIALS - Rody Putra Sartika (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2018)
This study aimed to describe the conceptual change of student before and after being taught through 5E learning cycle on the rate of reaction. One group pretest-posttest design was chosen as research design. The population consists of three classes students during the academic year of 2016/2017. According to saturation sampling technique, all of population then was chosen as samples. CRI Aided Achievement test was utilized to collect data about students’ conceptual change. The result showed that the conceptual shift was successfully confirmed. It was described according to five objectives. They were 1) objective of determining of the order of reaction which students gained 18.75 % improvement; 2) objective of determining the rate law which students gained 46.88 % improvement; 3) objective of determining the rate constant which students gained 15.62 % improvement; 4) objectives of determining the rate of a reaction which students gained 9.37 % improvement; and 5) objectives of determining the half-life which students gained 62.50 % improvement.